Bmi‐1 Epigenetically Orchestrates Osteogenic and Adipogenic Differentiation of Bone Marrow Mesenchymal Stem Cells to Delay Bone Aging - Jingyu Zhao; Ao Chen; Rong Wang; Dong Qiu; Haiyun Chen; Jiyu Li; Jin'ge Zhang; Tianxiao Wang; Yue Wang; Yujie Lin; Jiawen Zhou; Yifei Du; et al. (Advanced Science)
Abstract With the increase in the aging population, senile osteoporosis (SOP) has become a major global public health concern. Here, it is found that Prx1 and Bmi‐1 co‐localized in trabecular bone, bone marrow cavity, endosteum, and periosteum. Prx1‐driven Bmi‐1 knockout in bone‐marrow mesenchymal stem cells (BMSCs) reduced bone mass and increased bone marrow adiposity by inhibiting osteoblastic bone formation, promoting osteoclastic bone resorption, downregulating the proliferation and osteogenic differentiation of BMSCs, and upregulating the adipogenic differentiation of BMSCs. However, Prx1‐driven Bmi‐1 overexpression showed a contrasting phenotype to Prx1‐driven Bmi‐1 knockout in BMSCs. Regarding mechanism, Bmi‐1‐RING1B bound to DNMT3A and promoted its ubiquitination and inhibited DNA methylation of Runx2 at the region from 45047012 to 45047313 bp, thus promoting the osteogenic differentiation of BMSCs. Moreover, Bmi‐1‐EZH2 repressed the transcription of Cebpa by promoting H3K27 trimethylation at the promoter region −1605 to −1596 bp, thus inhibiting the adipogenic differentiation of BMSCs. It is also found that Prx1‐driven Bmi‐1 overexpression rescued the SOP induced by Prx1‐driven Bmi‐1 knockout in BMSCs. Thus, Bmi‐1 functioned as a hub protein in the epigenetic regulation of BMSCs differentiation to delay bone aging. The Prx1‐driven Bmi‐1 overexpression in BMSCs can be used as an approach for the translational therapy of SOP.